2011
DOI: 10.1177/0145482x1110501015
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Cues Used for Wayfinding in Urban Environments by Individuals with Visual Impairments

Abstract: This study examined which olfactory cues individuals with visual impairments use most often and determined which of these cues these individuals deemed to be the most important for wayfinding in urban environments. It also investigated the ways in which the individuals use these olfactory cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…Instead, there are only reports that humans can track odors [7] and that the visually impaired use odors to recognize locations [44]. Until now there has been no empirical evidence that humans can map an arbitrary location using only odors, an ability we have established in the present study.…”
Section: Resultsmentioning
confidence: 63%
“…Instead, there are only reports that humans can track odors [7] and that the visually impaired use odors to recognize locations [44]. Until now there has been no empirical evidence that humans can map an arbitrary location using only odors, an ability we have established in the present study.…”
Section: Resultsmentioning
confidence: 63%
“…Participants became better with practice and it could even be demonstrated that there is spatial discrimination of scent locations due to the (minimally) spatially separated nostrils (for the latter finding, see also Porter, Anand, Johnson, Khan, & Sobel, 2005). Olfactory landmarks have also been addressed in studies on how visually impaired people find their way in everyday life (e.g., Koutsoklenis & Papadopoulos, 2011).…”
Section: Olfactory Cues In Landmark-based Wayfindingmentioning
confidence: 99%
“…Koutsoklenis and Papadopoulos () state that the role of olfaction during way‐finding relates to the direction of the wind, the stability of the odors to which one is attuned, and other distracting smells in the environment. They state that “smells also come from natural elements (the ground, sea, and trees, for example), from animals (such as horses), and from other objects or attributes that produce distinctive smells (like a garbage can or a sewer)” (Koutsoklenis & Papadopoulos, , p. 699). On the contrary, the İzmir Fair Park cannot provide any of these sensory inputs to the participants in terms of smell and air movement.…”
Section: Resultsmentioning
confidence: 99%
“…This environment offers a homogeneous smell of a green environment and there were no other sources of smell. Koutsoklenis and Papadopoulos (2011) state that the role of olfaction during way-finding relates to the direction of the wind, the stability of the odors to which one is attuned, and other distracting smells in the environment. They state that "smells also come from natural elements (the ground, sea, and trees, for example), from animals (such as horses), and from other objects or attributes that produce distinctive smells (like a garbage can or a sewer)" (Koutsoklenis & Papadopoulos, 2011, p. 699).…”
Section: Findingmentioning
confidence: 99%